The Strength of Very Soft Clay Reinforced with Singular Bottom Ash Column - Muzamir, Hasan; Aminaton, Marto; Hyodo, Masayuki; Ahmad Mahir, Makhtar (2011)
In construction industry, the utilization of by-products or waste is one of the methods to achieve sustainable development. Stone column is a method where some of the soil is being replaced with granular material such as crushed rocks or sand. Stone columns usually installed in soft cohesive soil to improve bearing capacity, reduce settlement, and accelerate the dissipation of pore water pressure. Since the properties of bottom ash are almost similar to sand, there is a potential of using this material as granular material in stone column. By using bottom ash as stone column, generally it will significantly reduce the cost of a project and also solve the disposal problem for bottom ash since the material is considered as waste. In this study, four batches of kaolin samples with undrained shear strength of less than 10 kPa were tested on the shear strength after being inserted with bottom ash column. Each batch produced three specimens, tested to represent specimens without columns, specimens with partially penetrating bottom ash column and specimens with fully penetrating bottom ash column. A total of 12 unconfined compression tests had been conducted on one-dimensionally consolidated kaolin specimens. The specimens used for this test were 50 mm in diameter and 100 mm in height. The diameter for the column was 10 mm and the height of the column chosen for this study was 60 mm and 100 mm. The results show that the shear strength of the specimens was improved with the installation of bottom ash. However, for partially penetrating column, the value of shear strength increased more significantly compared to the fully penetrating column, although the fully penetrating column possessed higher column penetration ratio.